Imagining Joyce and Derrida : Between Finnegans Wake and Glas. - Mahon, Peter (University of Toronto Press, 2007)
Using key texts of Vico, Kant, and Heidegger, Mahon develops a theoretical framework that allows him to theorize and re-conceptualize the intertextuality between Joyce and Derrida in terms of the imagination.